Legal Protection of Children in Cases of Domestic Violcen: Case study of the East Aceh DP3AKB Service - Mareta, Anggun; Zakyyah, Zakyyah; Ridwansyah, Muhammad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The study focuses on studying and understanding the role and legal protection of the DP3AKB of East Aceh Regency. Then find out how the efforts and obstacles of the DP3AKB of East Aceh Regency in guaranteeing legal protection for children, and finally how should legal protection against child violence be in the DP3AKB of East Aceh Regency. This study uses empirical normative research with a focus on the legislative approach, conceptual approach, and philosophical approach. The results of the study are as follows: First, that the role of the DP3AKB of East Aceh Regency has normatively and legally mandated that children must be guaranteed and protected by law. This is also mandated by Law Number 35 of 2014 concerning Child Protection, Presidential Regulation Number 65 of 2020 concerning the Ministry of Women and Child Protection. Aceh Qanun Number 11 of 2008 concerning Child Protection. Second, in the implementation of the work program of the DP3AKB of East Aceh Regency, efforts have been made to map out efforts and obstacles in guaranteeing legal protection. Among other things, the DP3AKB of East Aceh Regency must carry out innovations in integrated community-based child protection (PATBM). Third, the ideal concept of legal protection against child violence in DP3AKB East Aceh Regency philosophically means Law Number 35 of 2014 concerning Child Protection which states that every child has the right to survive, grow and develop and has the right to protection from violence and discrimination. Suggestions to stakeholders are as follows: It is expected that DP3AKB East Aceh Regency will optimize its role, function and duties as a public servant so that the guarantee of legal protection for children in cases of domestic violence, sexual violence cases, and others are resolved through court and non-court mechanisms. [Penelitian memfokuskan mengkaji dan memahami bagaimanakah peranan dan perlindungan hukum DP3AKB Kabupaten Aceh Timur. Kemudian mengetahui bagaimana upaya dan kendala DP3AKB Kabupaten Aceh Timur dalam menjamin perlindungan hukum terhadap anak, dan terakhir bagaimana seharusnya perlindungan hukum terhadap kekerasan anak di DP3AKB Kabupaten Aceh Timur. Penelitian ini menggunakan penelitian normatif empiris dengan fokus pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan filosofis. Hasil penelitian sebagai berikut:  Pertama, bahwa peranan DP3AKB Kabupaten Aceh Timur sudah secara normatif yuridis mengamanahkan bahwa anak harus terjamin dan dilindungi oleh hukum. Hal ini juga diamanahkan Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak, Peraturan Presiden Nomor 65 Tahun 2020 tentang Kementerian Perempuan dan Perlindungan Anak. Qanun Aceh Nomor 11 Tahun 2008 tentang Perlindungan Anak. Kedua, dalam implementasi program kerja DP3AKB Kabupaten Aceh Timur sudah berupaya memetakan upaya dan kendala dalam menjamin perlindungan hukum. Antara lain, DP3AKB Kabupaten Aceh Timur harus melakukan inovasi perlindungan anak terpadu berbasis masyarakat (PATBM). Ketiga, konsep ideal perlindungan hukum terhadap kekerasan anak di DP3AKB Kabupaten Aceh Timur secara filosofis makna dari Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak yang menerangkan bahwa setiap anak berhak atas kelangsungan hidup, bertumbuh dan berkembang serta berhak atas perlindungan dari kekerasan dan diskriminasi. Saran kepada pemangku kepentingan sebagai berikut: Diharapkan kepada DP3AKB Kabupaten Aceh Timur mengoptimalkan peran fungsi dan tugasnya sebagai pelayan masyarakat sehingga penjaminan perlindungan hukum terhadap anak dalam kasus KDRT, kasus kekerasan seksual, dan lain-lain diselesaikan lewat mekanisme pengadilan dan non pengadilan.]